THE ROLE OF ZAHIRIDDIN MUHAMMAD'S SPIRITUAL HERITAGE IN EDUCATING YOUNG PEOPLE IN A SPIRIT OF PASSION - Mamadjonova Marvarid Qurbonazarovna (Journals Park Publishing, 2024)
Patriotism is a moral concept that refers to a person's love for his Father, his passion for preserving him, his responsibility and duty to godly devotion. The development of any society is associated with a sense of patriotism in each individual. Patriotism is the spiritual basis of the life of each state and is portrayed as the most important mobilizing force in the development of society in all aspects. [1].